Mosaicing of multiplanar regions through autonomous navigation of off‐the‐shelf quadcopter. Issue 3 (12th September 2019) - Prasad, Meghshyam G.; Akula, Sona Praneeth; Vemula, Anirudh; Chandran, Sharat
Abstract : The real world is made up of multiplanar and curved surfaces. Imaging such surfaces with an orthographic view using a handheld camera is tiring if the scene encompasses a view larger than the camera field of view. If the scene is geographically beyond the reach of humans, or access to the scene is denied, it is not possible to take such a frontal view of the scene from handheld devices. The advent of inexpensive flying vehicles such as quadcopters enables the orthographic imaging of large surfaces for later analysis either for leisure or serious scientific purposes. However, manual navigation of the quadcopter around such surfaces is tedious and results are not satisfactory. In this paper, the authors present a method for autonomous navigation of a quadcopter for imaging multiplanar surfaces. The proposed method builds on the existing parallel tracking and mapping based approach to create an approximate sparse three‐dimensional map of the input scene. Next, the authors determine precise locations for obtaining videos for each bounded plane, and then autonomously manoeuver the quadcopter at these waypoints. This results in an end‐to‐end application for visualising scenes with an off‐the‐shelf quadcopter.